Generic daclatasvir plus sofosbuvir, with or without ribavirin, in treatment of chronic hepatitis C: real‐world results from 18 378 patients in Egypt. Issue 3 (29th November 2017) - Omar, H.; El Akel, W.; Elbaz, T.; El Kassas, M.; Elsaeed, K.; El Shazly, H.; Said, M.; Yousif, M.; Gomaa, A. A.; Nasr, A.; AbdAllah, M.; Korany, M.; et al.
Summary: Background: Treatment of chronic hepatitis C using combination of sofosbuvir (SOF) and daclatasvir (DCV) was used in several clinical trials and multicentre studies, which were somewhat limited to genotypes 1‐3. The national program in Egypt is using SOF‐DCV combination for large scale treatment. Aim: To assess the efficacy and safety of combined SOF‐DCV in treating patients with HCV‐G4 in a real‐world setting. Methods: Data and outcome of chronic HCV patients who were treated for 12 weeks with generic medications: DCV 60 mg plus SOF 400 mg ± ribavirin (RBV) within the national hepatitis C treatment program in Egypt are presented. Treatment‐naïve patients without cirrhosis were treated without RBV, and those who had cirrhosis or were treatment‐experienced (interferon experienced or SOF experienced) received RBV. Efficacy and safety were assessed, and baseline factors associated with sustained virological response at post‐treatment week 12 (SVR12) were explored. Results: During the first 2 months of the programme, 18 378 patients with HCV‐G4 started treatment with SOF‐DCV with or without RBV. Overall, 95.1% achieved SVR12 (95.4% among patients treated without RBV and 94.7% for patients treated with RBV, P = .32). Treatment was prematurely discontinued in only 1.5% of patients. The most common events leading to discontinuation were patient withdrawal ( n = 76) and pregnancy ( n = 5). Five deaths occurred within this group. Conclusions: Real‐world experience of generic SOF‐DCV in patients with chronic HCV‐G4 proved to be safe and associated with a high SVR12 rate, in patients with different stages of fibrosis. Abstract : Linked Content This article is linked to El Kassas et al paper. To view this article visit https://doi.org/10.1111/apt.14628 .